Anthony Browne’s picture-books in their original language: new classics in French primary schools? - Burgain, Marie-France (Ondina - Ondine, 2023)
If being awarded literary prizes is part of what makes a classic and if school is a place which recognizes classics, the British writer and illustrator Anthony Browne, who has been awarded many prizes for his picture-books and for his whole career as an illustrator, present among the writers studied in French primary schools, really deserves to be called a classic. Besides, he has known a new form of recognition for about fifteen years : his books, in English, have become classics of the English as a foreign language class. Many of his picture-books belong to the set of books used by primary school teachers in their English class and a method about how to teach English as a foreign language with the books by Anthony Browne has been published. The question now is to know how to study these classics while taking into account the fact they have been written in English first. Thus, reading them will enable French pupils to discover new aspects of Anthony Browne’s books. Thanks to the games they offer their readers, these picture-books can then be analysed from a linguistic and cultural but also literary and artistic perpective. Key-words: Picture-books, Anthony Browne, classics, original language, literary and artistic culture.